2018
DOI: 10.1002/gj.3254
|View full text |Cite
|
Sign up to set email alerts
|

Sequence architecture and depositional evolution in Lufeng Depression, Pearl River Mouth Basin, South China Sea Part B: The shore deposits of Zhuhai Formation

Abstract: The Zhuhai Formation in Lufeng Depression is mainly deposited during a depression stage. In this paper, we employ cores, wireline logs, and seismic reflections to reveal sequence architecture and depositional evolution in target intervals. The results indicated that one second‐order sequence and two third‐order sequences were identified and sequence stratigraphic framework was established. The second‐order sequence was developed in response to base‐level falling, while third‐order sequences were mainly formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Previous studies have demonstrated that there are several classification schemes for the late Palaeogene depositional sequences due to geological and geophysical datasets limitations (Ge, Zhu, Li, et al, ; Ge, Zhu, Zhang, et al, ; Jiao et al, ; Tao et al, ; Z. H. Wang et al, ;Xia, Dong, et al, ; Xia, Liu, et al, ). Among all these classification schemes, it can be generally summarized into two schemes.…”
Section: Sequence Architectures and Depositional Evolutionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that there are several classification schemes for the late Palaeogene depositional sequences due to geological and geophysical datasets limitations (Ge, Zhu, Li, et al, ; Ge, Zhu, Zhang, et al, ; Jiao et al, ; Tao et al, ; Z. H. Wang et al, ;Xia, Dong, et al, ; Xia, Liu, et al, ). Among all these classification schemes, it can be generally summarized into two schemes.…”
Section: Sequence Architectures and Depositional Evolutionsmentioning
confidence: 99%
“…Among all these classification schemes, it can be generally summarized into two schemes. The depositional sequence is conducted based on the differences in thin sections, cores, wireline logs, and seismic sections in some researches (Jiao et al, ; Tao et al, ; Z. H. Wang et al, ; Xia, Dong, et al, ; Xia, Liu, et al, ). In other researches, it is classified according to the variations in stratal architecture (unconformity and correlative conformity, fault throw, and strata thickness; Ge, Zhu, Li, et al, ; Ge, Zhu, Zhang, et al, ).…”
Section: Sequence Architectures and Depositional Evolutionsmentioning
confidence: 99%
See 3 more Smart Citations